Inhibiting protein-protein interactions 1 - Whitty, Adrian (Henry Stewart Talks, 2014)
The druggable proteome, Objectives, Five propositions about the druggability of PPI targets, Classification of PPI targets, Why are small molecule inhibitors of PPI hard to obtain?, PPI topology can vary widely, Classification of PPI interfaces, Druggability, Fragment-based lead identification, Empirical measures of druggability, Factors affecting druggability, Computational assessment of PPI druggability with FTMAP, Evaluating PPI using FTMAP, Nature of druggable sites in PPI